TRANSFORMATION OF HUMAN RESOURCES COMPETENCE FOR THE STRENGTHENING OF GOOD GOVERNANCE THROUGH QUALITY GROUP RAPPORTS - Gede Sanjaya Adi Putra; I.B. Putra Manuaba; Anand Yamani Yupitrika (Faculty of Economics and Business, Universitas Warmadewa, 2024)
This study aims to determine how “The Role of HR Competencies in Improving Good Governance Through Superior Financial Reporting in village governments” in village governments in the Denpasar city area. The type of research conducted is using an associative approach. The population in the study were all villages in the Denpasar city government area. Respondents used were village government officials selected by purposive sampling in the city of Denpasar. This study consists of independent variables of human resource quality, with dependent variables of good governance and intervening variables of financial reporting quality. Data analysis techniques used in this study are descriptive analysis, variance-based Structural Equation Modeling (SEM) analysis (Partial Least Square). The hypotheses in this study are; (1) there is an effect of the quality of human resources on good governance. (2) the quality of financial reporting can mediate the effect of human resource competence on good governance. The conclusion obtained in this study is that HR competence does not have a significant effect on GCG, but the quality of financial reports is able to mediate the relationship between HR competence and Good Governance.